Rakes, highwaymen, and pirates : the making of the modern gentleman in the eighteenth century - Mackie, Erin Skye, 1959- (Johns Hopkins University Press, 2009)
Synthesizing the histories of masculinity, manners, and radicalism, Rakes, Highwaymen, and Pirates offers a fresh perspective on the eighteenth-century aristocratic male.